Unknown publication about Francisk Skorina’s works - Nemirovskij, Jevgenij (Knygotyra, 1988)
Included are data about unknown book trade announcements from 1786 and a short article by historian and bibliographer L. I. Bacmeister, which first introduced a number of Francisk Skorina’s publications into scientific practice.